Sombras negras: a imagem de autor em Recordações do Escrivão Isaías Caminha, de Lima Barreto - Chaves, Ramon Silva (2014)
This study is inserted in the theoretical and methodological postulates of the discourse analysis in French lines and has as theme the exam of the image of Author in Recordações do Escrivão Isaías Caminha by Lima Barreto. This theme shows itself relevant because we observe the literary discourse by the enunciative-dircursive perspective which allocates the Author as subject who, inunciatively, projects his own image in the polemically of the discourse. It can be noticed by the unveiling of the topical and non-topical units and that have extrinsic representation to the literary enunciation. For this purpose, we will build on the concepts attendant Maingueneau, such as the Author and The Image of Author, Literary Discourse and scenography. The proposed analysis founded itself in a theoretical and methodological procedure in which the scenography established the topical and non-topical units, which reveal in the selected literary discourse, by paratopic via, an Image of the Author.Our study identified an Image of Author which emerges enunciative and discoursively in Recordações do Escrivão Isaías Caminha as a shadow which reveals nuances of contrasts, acts, actions and discoursive formations of black and mulatto from the late nineteenth century and early twentieth century